CASTRATION OF NELLORE CATTLE IN FEEDLOT FINISHING DIETS - Melo, Gabriel Fernandes de [UNESP]; Coneglian Brichi, Andre Luis [UNESP]; Costa, Carolina Floret da [UNESP]; Rizzieri, Ramon Argentini [UNESP]; Ferreira Miranda, Lucas Domingos [UNESP]; Perdigao, Alexandre [UNESP]; Millen, Danilo Domingues [UNESP]; Martins, Cyntia Ludovico [UNESP]; Arrigoni, Mario de Beni [UNESP] (Inst Zootecnia, 2020)
The objective of the present study was to evaluate the performance and carcass characteristics of Nelore bulls and steers, finished in feedlot with high concentrate diet. Thirty-six male Nelore cattle with 24 months old, from rearing in a continuous grazing system were divided into two groups of 18 animals (castrated and non-castrated) with initial mean body weight (iBW) of 347.5 kg +/- 21.61 kg. The experimental design was a randomized complete block according to iBW for each sexual condition evaluated, constituting two experimental treatments: castrated animals and non-castrated animals. Each treatment consisted of six pens ( 3 animals/pen), these being considered the experimental units. The feedlot period was 112-days and the slaughter was carried out on the 113th day. The dry matter intake (DMI), average daily gain (ADG), feed conversion (F:G) and feed efficiency (G:F) were evaluated. In addition, the deposition of muscular and adipose tissue was evaluated by means of ultrasonography. After slaughtering of the animals the hot carcass weight (HCW), cold carcass weight (CCW) and carcass yield (YG) were determined. The data were analyzed using the PROC MIXED program from SAS and Tukey test (P = 5%). There was no significant difference for the variables iBW and DMI in percentage of BW. The fBW, ADG, F:G and G:F variables had significant effects, and the group of non-castrated animals obtained a better productive performance. For the carcass traits evaluations, a significant difference was observed for HCW and CCW, where animals from the non-castrated group also had better carcass data. Therefore, it is concluded that for feedlot systems with high concentrate diets, castration of Nellore cattle is not recommended because it interfered negatively in the productive performance of the castrated animals.